1978
DOI: 10.1126/science.202.4364.215
|View full text |Cite
|
Sign up to set email alerts
|

Beryllium-10 Mass Spectrometry with a Cyclotron

Abstract: The Grenoble cyclotron has been used as a mass spectrometer to measure ratios of beryllium-10 to beryllium-9 of 10(-8), 10(-9), and 10(-10) in standardized beryllium oxide samples. Similar measurements can be used to determine cosmogenic beryllium-10 (half-life, 1.5 x 10(6) years) profiles in various geophysical reservoirs such as sea sediments and polar ice. This procedure can be used either to date such samples or to give information about geophysical and astrophysical phenomena that have influenced the bery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The pioneering AMS measurements of 10 Be utilized a cyclotron (Raisbeck et al 1978) and resulted in substantial increases in sensitivity. Raisbeck et al demonstrated that 10 Be/ 9 Be ranging from 10 -8 to 10 -10 could be easily measured achieving a detection sensitivity of ~10 9 atoms.…”
Section: Isotopic Analysis Of 10 Bementioning
confidence: 99%
“…The pioneering AMS measurements of 10 Be utilized a cyclotron (Raisbeck et al 1978) and resulted in substantial increases in sensitivity. Raisbeck et al demonstrated that 10 Be/ 9 Be ranging from 10 -8 to 10 -10 could be easily measured achieving a detection sensitivity of ~10 9 atoms.…”
Section: Isotopic Analysis Of 10 Bementioning
confidence: 99%
“…The nuclear accelerator mass spectrometry developed in recent years (e.g., Muller, 1977;Raisbeck et al, 1978; Heath, G.R., Burckle, L.H., et al, Init. Repts.…”
Section: Introductionmentioning
confidence: 99%
“…A solution is offered here by accelerator mass spectrometry (AMS) developed 0.1 in the late 1970s [e.g., 12,13,14,15]. With this method, the radionuclides of interest are identified in terms of their mass and nuclear charge and not in terms of their decay processes.…”
Section: Introductionmentioning
confidence: 99%